Determinants of Health Service Utilization Among Users of Dokolo Health Centre IV, Dokolo District: A Community Perspective - Ojok, Francis; Samuel Mukasa, Samuel; Omona [PhD], Kizito (International Journal of Health, 2021)
Introduction: Health services utilization (HSU) is an important health outcome indicator, a surrogate measure of access to healthcare that influences the outcomes of health status and consumer satisfaction. Healthcare is central to community well-being as well as a fundamental aspect of life. Objective: The study sought to assess determinants of health service utilization among users of Dokolo Health Centre IV, Dokolo district. Methods: A cross sectional analytical design, which employed both quantitative and qualitative approaches, was used between January and July, 2020. A total of 396 respondents participated. Data was collected using Semi-structured questionnaires and Focus Group Discussion guide. Analysis was done using SPSS and qualitative data was analyzed verbatim.Results: Only 26.8% of the users were satisfied with services provided in the health facility. Living environments of respondents was the only socio-demographic factor that determined HSU (p = 0.046). Living in urban area was 1.6 times more likely to be a determinant of HSU than living in rural setting [COR=1.571, 95% CI (0.986-2.504)]. The study found that being a female was 1.14 times more likely to utilize health services (COR=1.135, 95% CI (0.741-1.739)). Similarly, majority of the respondents who were peasants, 174(43.9%), utilized health services from the facility as opposed to their formally employed counterparts. Thus, being formally employed was 0.7 times less likely to utilize health services (COR= 0.655, 95% CI (0.29-1.476)). Satisfaction with services (p=0.000), level of satisfaction (p=0.000) and distance to health facility (p=0.033) were enablers of HSU. Being very satisfied was 16 times more likely for one to utilize health services [COR=16, 95% CI (0.000- 0.001)]. Most of the respondents rated the quality of care as poor.Conclusion: Health service utilization remains quite low in many rural health facilities of Uganda.Â Â